INFLUENCE OF HMI ERGONOMY ON DRIVERS IN COOPERATIVE SYSTEMS AREA - Tomáš Jizba (Acta Polytechnica CTU Proceedings)
Modern vehicles are getting smarter and utilize more and more the advantages of Advanced Driver Assistance Systems (ADAS). Deployment of upcoming technologies, such as cooperative systems (V2X), will most likely be the key step towards a significant reduction of accidents across the globe. Some of these systems extend driver’s field of vision, so the driver can be forewarned against a wide range of threats. Unlike technology, the human processing capacity has remained almost unchanged over centuries. Therefore, it is necessary to bear in mind that drivers have restricted capabilities to process multiple warnings. In this context, an important question arises: How can be V2X warnings integrated into the Human Machine Interface (HMI) of vehicles, and what warning policy is needed to ensure high usability, acceptance, efficiency and understanding of such a warning interface from the driver’s point of view. Using a human centered design approach, two concepts of visual driver-vehicle interface for V2X warnings were developed and evaluated. One of those interfaces was based on a 1-stage warning policy and the second one utilized a dynamic 3-stage warning approach. The research revealed that drivers prefer to have dynamic warnings that correspond with the level of danger to which they are exposed, rather than only one warning displayed in a situation of imminent danger. However, with regards to overall usability score and workload measurements, results showed that the 3-stage system performed worse in comparison with the 1-stage system.